The importance of social responsibility in the pymes - Calle Herencia, Cesar Alonso (2022)
The purpose of the study was to address the concept of Corporate Social Responsibility (CSR), applied in the practice of Micro and Small Enterprises (SMEs), in light of the advances and limitations of responsible business practices and to determine its particular link with the sustainable development. From the bibliographic review referring to the analysis and evaluation of CSR that various institutions, companies and universities have been carrying out on the socially responsible behavior of companies in Peru, it has been found that CSR is still an incipient practice in the actions of companies, whatever their size and nature. Labor legislation is one of the most harmful in relation to international conventions and agreements; labor rights are not guaranteed in business practice. Considering that in our country SMEs are the main engine of the economy by creating employment and income conditions for broad sectors of the population, especially the poorest, and they constitute agents of social change in participatory processes, it has been confirmed that the fundamental aspects of CSR such as environmental performance, compliance with social standards, image in the community, company-community linkage, do not have any impact on the management structures of SMEs.